Addressing Street Children, Vagrants, and Beggars through the Role of Community Social Workers in Yogyakarta A Practical and Theoretical Approach - Niswatun Hasanah; Karimah, Fatha (UIN Sunan Kalijaga Yogyakarta, 2024)
This paper aims to address the increasing phenomenon of social problems in society, such as street children, homeless individuals, and beggars, which require serious attention. This phenomenon is of particular interest to be studied in depth in order to find appropriate solutions for these social issues. One of the key players in addressing these problems is social volunteers, also known as Community Social Workers. This research focuses on the role of Community Social Workers in handling street children, the homeless, and beggars in Yogyakarta. Using a descriptive qualitative approach, this paper analyzes the role of Community Social Workers based on Ministerial Regulation No. 10 of 2019. The study highlights the importance of collaboration between Community Social Workers and government social institutions in Yogyakarta. The findings indicate that the role of Community Social Workers in addressing these social issues reflects their empathy, care, and dedication to serving the community of Yogyakarta. Keywords: Community Social Workers, Street Children, Homeless, Beggars, Social Tulisan ini bertujuan untuk menjawab fenomena meningkatnya permasalahan sosial di masyarakat, seperti anak jalanan, gelandangan, dan pengemis, yang membutuhkan penanganan serius. Fenomena ini menarik untuk dikaji lebih dalam guna menemukan solusi yang tepat dalam mengatasi permasalahan sosial tersebut. Salah satu pihak yang berperan dalam penanganan masalah ini adalah relawan sosial, atau yang dikenal sebagai Pekerja Sosial Masyarakat. Penelitian ini berfokus pada peran Pekerja Sosial Masyarakat dalam menangani anak jalanan, gelandangan, dan pengemis di Yogyakarta. Menggunakan pendekatan kualitatif deskriptif, tulisan ini menganalisis peran Pekerja Sosial Masyarakat berdasarkan Peraturan Menteri Sosial Nomor 10 Tahun 2019. Penelitian ini menekankan pentingnya kerjasama antara Pekerja Sosial Masyarakat dengan lembaga-lembaga sosial pemerintah di Kota Yogyakarta. Hasil penelitian menunjukkan bahwa peran Pekerja Sosial Masyarakat dalam menangani permasalahan sosial ini merupakan wujud empati, kepedulian, dan jiwa pengabdian terhadap masyarakat Kota Yogyakarta. Kata Kunci: Pekerja Sosial Masyarakat , Anak Jalanan, Gelandangan, pengemis, sosial